Three Layers of Workplace Well-Being: Job Design, Job Crafting, and Individual Well-being Behaviors - Sabine Sonnetag (European Health Psychologist, 2026)
While work provides opportunities for personal development and growth, it can also harm individual well-being. This article presents a three-layered approach to workplace well-being. It argues that if we want to take workplace well-being seriously and want to improve it, we need to consider the three layers of job design (i.e., objective features of a job as set by top-down organizational processes), job crafting (i.e., employees’ deliberate efforts to change features of their jobs), and individual well-being practices (i.e., spontaneous and intervention-driven stress management approaches). This article describes the conceptual foundations of the three layers and presents empirical evidence on the benefits of improving job design, job crafting, and well-being practices. It discusses interconnections between the three layers, demonstrating their interdependence in people’s work lives.